2016
DOI: 10.1080/10095020.2016.1260811
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of transit trip production using Factorial Kriging with External Drift: an aggregated data case study

Abstract: Studies in transportation planning routinely use data in which location attributes are an important source of information. Thus, using spatial attributes in urban travel forecasting models seems reasonable. The main objective of this paper is to estimate transit trip production using Factorial Kriging with External Drift (FKED) through an aggregated data case study of Traffic Analysis Zones in São Paulo city, Brazil. The method consists of a sequential application of Principal Components Analysis (PCA) and Kri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 20 publications
0
9
0
11
Order By: Relevance
“…This geo-statistic model has been present as a predictor model in different investigations related to transport networks (Lindner, Pitombo, Rocha, & Quintanilha, 2016;Moncada, Cardona, & Escobar, 2018;Prasetiyowati, Imrona, Ummah, & Sibaroni, 2016).…”
Section: Stagementioning
confidence: 99%
“…This geo-statistic model has been present as a predictor model in different investigations related to transport networks (Lindner, Pitombo, Rocha, & Quintanilha, 2016;Moncada, Cardona, & Escobar, 2018;Prasetiyowati, Imrona, Ummah, & Sibaroni, 2016).…”
Section: Stagementioning
confidence: 99%
“…For the construction of the isochrones curves of global average accessibility and gradient savings, for the current situation and the different analyzed scenarios, the ordinary Kriging geo-statistical model is used, with a linear semi-variogram as a structural equation (Díaz Viera, 2002;Oliver & Webster, 1990), which has been used in various investigations on issues related to transport (Escobar et al, 2018a, Lindner, Pitombo, Rocha, & Quintanilha, 2016Zhang & Wang, 2014). In this case, the average time travel vectors are used as interpolation input, in the case of the global average accessibility and the savings gradient vectors, in the case of the savings gradient.…”
Section: Construction Of Isochrones Curves Of Global Average Accessibmentioning
confidence: 99%
“…Some recent studies showed the potential of geostatistics in terms of enabling the interpolation of transportation demand variables and the understanding of the spatial distribution by maps of kriging predicted values (Pitombo et al 2015a, b;Lindner et al 2016). However, it must be pointed out that there is a need for adapting to travel variables given that they are generally discrete variables and have no spatial continuity.…”
Section: Introductionmentioning
confidence: 99%